2018
DOI: 10.1007/s00580-018-2832-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of royal jelly on the DNA integrity of sperms and early in vitro embryonic development in ofloxacin treated rats

Abstract: Background: Pyridaben, a pyridazinone derivative, is a new acaricide and insecticide for control of mites and some insects such as white flies, aphids and thrips. Objective: This study was designed to elucidate how pyridaben can affect the sperms' morphological parameters, its DNA integrity, and to estimate the effect of various quantities of pyridaben on in vitro fertilization rate. Materials and Methods: In this study, 80 adult male Balb/C strain mice were used. Animals were divided into control and two test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In recent years, studies have repeatedly reported that environmental pollutants interfere at different levels with the physiology of organisms, inducing alterations in development and reproduction (Salazar‐Aredondo et al, ; Capriglione et al, ; Perry et al, ; ACOG, ; Tussellino et al, ; Pallotta et al, ). Overexposure to chemical agents, heavy metals and pesticides, present in the environment or introduced into the bodies by feeding, has been demonstrated to reduce sperm quality, acting on spermatozoa counts and lowering percentages of normal mammalian sperm (Selvaraju et al, ; Ebadi Manas, ; Chiu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have repeatedly reported that environmental pollutants interfere at different levels with the physiology of organisms, inducing alterations in development and reproduction (Salazar‐Aredondo et al, ; Capriglione et al, ; Perry et al, ; ACOG, ; Tussellino et al, ; Pallotta et al, ). Overexposure to chemical agents, heavy metals and pesticides, present in the environment or introduced into the bodies by feeding, has been demonstrated to reduce sperm quality, acting on spermatozoa counts and lowering percentages of normal mammalian sperm (Selvaraju et al, ; Ebadi Manas, ; Chiu et al, ).…”
Section: Introductionmentioning
confidence: 99%